Keshan Disease: A Potentially Fatal Endemic Cardiomyopathy in Remote Mountains of China - Shi, Ying; Yang, Wei; Tang, Xianwen; Yan, Quanhao; Cai, Xiaojing; Wu, Fenfang (Frontiers in Pediatrics, 2021)
Keshan disease (KD) as an endemic, highly lethal cardiomyopathy, first reported in northeast China's Keshan County in 1935. The clinical manifestations of patients with KD include primarily congestive heart failure, acute heart failure, and cardiac arrhythmia. Even though some possible etiologies, such as viral infection, fungal infection, microelement deficiency, and malnutrition, have been reported, the exact causes of KD remain poorly known. The endemic areas where KD is found are remote and rural, and many are poor and mountainous places where people are the most socioeconomically disadvantaged in terms of housing, income, education, transportation, and utilization of health services. To date, KD is a huge burden to and severely restricts the economic development of the local residents and health systems of the endemic areas. Although efforts have been made by the government to control, treat, and interrupt disease transmission, the cure for or complete eradication of KD still requires global attention. For this reason, in this review, we systematically describe the etiological hypothesis, clinical manifestations, incidence characteristics, and treatment of KD, to facilitate the better understanding of and draw more attention to this non-representative cardiovascular disease, with the aim of accelerating its elimination.